A validated photonumeric cellulite severity scale for the area above the knees: the knee cellulite severity score. (20th March 2020) - Longhitano, S.; Galadari, H.; Cascini, S.; Shaniko, K.; Chester, J.; Farnetani, F.; Pellacani, G.; Urtis, G.G.; Guida, S.
Abstract: Background: Treatment for cellulite above the knees is increasingly requested. However, a classification of cellulite of this area has not yet been developed. Objective: To validate the proposed knee cellulite severity score (KCSS) for the assessment of cellulite and skin laxity above the knee. Materials and methods: Based on standardized photographs of cellulite and skin laxity above the knees of 57 females (114 knees), three key morphological aspects of cellulite were identified. A photonumeric KCSS was developed and validated by three independent assessors. Results: The three key cellulite morphological features (number of depressions, depth of depressions and presence of laxity) are each graded from 0 to 3, producing a classification of no lesions (0), mild (1–3), moderate (4–6) and severe (7–9). Evaluators at different time points repeated similar classifications (intraclass correlation coefficient >0.9), which were also similar among the assessors (inter‐observer reliability >0.9). All three key morphological aspects were deemed necessary, and positively contributed, to the overall scale (item‐total correlation analysis values >0.89, P  < 0.05). Conclusions: The KCSS is a consistent, comprehensive, reliable, and reproducible tool for standardized and objective assessment of the severity of cellulite and skin laxity above the knees.